Fundamentalidade e efetividade do direito humano à moradia adequada - Monteiro, Vitor de Andrade (2014)
The right to adequate housing is presented as an integral element of the concept of human dignity, true sine qua non condition for dignified existence. This right hás robust regulatory substrate in international law and in the domestic legal order. Because of the numerous international treaties adhered by Brazil recognizing that human right, it is Brazilian’s government obligation to develop concrete measures aimed its progressive implementation, including subjecting themselves to na international accountability. The comprehension of this right can not be limited to the viability of four walls and a roof, but it is necessary to implement the factors identified by the Committee on Economic, Social and Cultural Rights to characterize their suitability. The Federal Constitution, after the Constitutional Amendment No. 26, now provides explicitly the fundamental right to housing which enhances its relevance and urgency, giving to it all the legal privileged regimen of the fundamental rights, and in particular its immediate applicability and status of entrenchment clause. The meaning of the right to housing transcend their tangible aspect, involving a psychological and human dimension, so it can be seen not only as a physical location, but taking moral contours of a place where individuals develop as human beings. Housing policies developed in Brazil in the recent decades has not proven effective in tackling the housing deficit, since it has not turned its focus to low-income families, which represent almost 90 % of the Brazilian housing deficit. The result is the increasing social exclusion and concentration of wealth, and significant speculative activity, which tends to displace the poorest social classes to outlying urban areas, where there is scarcity of public services and living situation unworthy. In this context, it is pursuit the effectiveness of social housing in order to ensure the existential minimum. The way that this right was legally treated law allows its enforceability in the courts in the event of failure of the Administration or detrimental action implementation. Moreover, considering the scarcity of resources, especially observed in peripheral countries such as Brazil, it is indispensable to analyze the efficiency of public housing policy developed in order to maximize its effectiveness with the resources available.